Parole in Western Australia: an analysis of parole cancellations of female offenders - Catherine Ferguson (2015)
Foreword The number of prisoners in Australian prisons has been increasing over the past decade. In Western Australia the number of female offenders has increased by 40 percent over the past five years. One contributing factor to this increase may be the re incarceration of parolees who have violated parole. This research used the publicly available decision documents from the Prisoners Review Board in Western Australia to investigate the background details of offences, and the details of the parole violations of 41 women released in 2013–14. Data revealed that a high proportion of women returned to prison after a very short time in the community as a result of illicit drug use. The high cost of re-incarceration is considered against a background of rehabilitation and extra support in the community that might assist released women negotiate their complex lives on release without resorting to further drug use. The paper includes a number of recommendations to consider in an effort to reduce the recidivism of female offenders